2007
DOI: 10.1001/archneur.64.2.noc60131
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Outcome in Anticoagulation-Associated Cerebral Hematoma Requiring Emergency Evacuation

Abstract: To analyze the likelihood of recovery and prognostic factors in patients with massive anticoagulation-associated intracerebral hemorrhage treated with surgical evacuation after reversal of anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Due to the retrospective study design we do not have recanalization data and also did not systematically collect information regarding hyperdense MCA signs which have been shown to predict outcome in large rtPA registries [29]. The poor functional outcome of patients with a low combined score may have partially been due to a self-fulfilling prophecy as physicians may have limited patient care in early treatment phases due to expectation of a poor functional outcome [30,31]. We included patients who received additional IA therapies after initiation of IV thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the retrospective study design we do not have recanalization data and also did not systematically collect information regarding hyperdense MCA signs which have been shown to predict outcome in large rtPA registries [29]. The poor functional outcome of patients with a low combined score may have partially been due to a self-fulfilling prophecy as physicians may have limited patient care in early treatment phases due to expectation of a poor functional outcome [30,31]. We included patients who received additional IA therapies after initiation of IV thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid reversal of INR has also permits urgent surgical evacuations in neurologically deteriorating patients with anticoagulant related ICH. Early reversal and evacuation was associated with a high rate (65%) of favorable outcomes in patients with a prominent midline shift (with or without TTH) in one study [113].…”
Section: A Rapid Inr Reversal (Within 2 H)mentioning
confidence: 92%
“…Rapid reversal of international normalised ratios also enables urgent surgical evacuations in patients who are deteriorating neurologically with intracerebral haemorrhage related to oral anticoagulant use. One study 145 reported a high rate (65%) of favourable outcomes in patients with prominent midline shift (with or without uncal herniation) who had emergent surgical evacuation after reversal.…”
Section: Intracerebral Haemorrhage Related To Use Of Oral Anticoagulantsmentioning
confidence: 99%